Tocap: a web tool for ad-hoc campaign planning in terrestrial hydrology. Issue 2 (21st January 2022) - Nixdorf, Erik; Eggert, Daniel; Morstein, Peter; Kalbacher, Thomas; Dransch, Doris
Abstract: Planning an event-based monitoring campaign on the regional scale is challenging, e.g. the timing and location of monitoring visits can dramatically impact monitoring efficacy and depends on the optimal environmental conditions required by the measurement parameters and the overarching monitoring goal. Therefore we developed a generic campaign planning approach utilizing interactive visualization methods and implemented this approach into the component-based web tool called Tocap: Tool for Campaign Planning. As a case study, we determine the most suitable time and location for event-driven, ad-hoc monitoring in hydrology using soil moisture measurements as our target variable. Our approach supports: (1) data acquisition from various digital data sources, (2) identification of the most suitable locations for measurements, (3) identification of the most suitable time for measurements at the selected locations, and (4) planning an optimized monitoring route. HIGHLIGHTS: Development of an open-source web-based environment to explore and process time-variant datasets. Providing target variable computation by multiple linear regression and filter functions. Determining monitoring locations by visualizing time series of hydro-meteorological forecast data. Computation and export of a monitoring route using OpenStreetMap data. Demonstration of the framework for planning a soil moisture monitoring campaign.